Creation of Brønsted Acidity by Grafting Aluminum Isopropoxide on Silica under Controlled Conditions: Determination of the Number of Brønsted Sites and their Turnover Frequency for m‐Xylene Isomerization. Issue 3 (21st January 2014) - Caillot, Maxime; Chaumonnot, Alexandra; Digne, Mathieu; Van Bokhoven, Jeroen A.
Abstract There is not a unique Brønsted acid site for aluminosilicates (ASAs). IR spectroscopy following CO adsorption proves the creation of Brønsted acid sites on Al/SiO2 ASAs, which are synthesized by the deposition of aluminum species on hydroxylated silica. These sites are active for ethanol dehydration and m‐xylene isomerization. Controlled deposition under anhydrous conditions optimizes the number of sites, whereas the presence of water leads to alumina agglomerates with no Brønsted acidity. The turnover frequency for m‐xylene isomerization (4.3×10−4 s−1 site−1 at 350 °C, atmospheric pressure, and 0.6 cm3 h−1 of m‐xylene) is approximately 3 times lower than that of the Brønsted acid sites of Si/Al2O3 and 75 times lower than that of an ultrastable Y‐type zeolite without extra‐framework aluminum.